Can Event-Related Potentials Evoked by Heel Lance Assess Pain Processing in Neonates? A Systematic Review - Yui Shiroshita; Hikari Kirimoto; Mio Ozawa; Tatsunori Watanabe; Hiroko Uematsu; Keisuke Yunoki; Ikuko Sobue (MDPI AG, 2021)
To clarify the possibility of event-related potential (ERP) evoked by heel lance in neonates as an index of pain assessment, knowledge acquired by and problems of the methods used in studies on ERP evoked by heel lance in neonates were systematically reviewed, including knowledge about Aδ and C fibers responding to noxious stimuli and Aβ fibers responding to non-noxious stimuli. Of the 863 reports searched, 19 were selected for the final analysis. The following points were identified as problems for ERP evoked by heel lance in neonates to serve as a pain assessment index: (1) It is possible that the ERP evoked by heel lance reflected the activation of Aβ fibers responding to non-noxious stimuli and not the activation of Aδ or C fibers responding to noxious stimulation; (2) Sample size calculation was presented in few studies, and the number of stimulation trials to obtain an averaged ERP was small. Accordingly, to establish ERP evoked by heel lance as a pain assessment in neonates, it is necessary to perform a study to clarify ERP evoked by Aδ- and C-fiber stimulations accompanied by heel lance in neonates.